2013
DOI: 10.3402/ijch.v72i0.21530
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of food and water security in an Arctic Health context – results from an international workshop discussion

Abstract: In August 2012, a literature search with the aim of describing indicators on food and water security in an Arctic health context was initialized in collaboration between the Arctic Human Health Expert Group, SDWG/AHHEG and the AMAP (Arctic Monitoring and Assessment Programme within the Arctic Council) Human Health Assessment Group, AMAP/HHAG. In December 2012, workshop discussions were performed with representatives from both of these organizations, including 7 Arctic countries. The aim of this article is to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…It was a collaboration between the Arctic Human Health Expert Group, (AHHEG) and the Arctic Monitoring and Assessment Programme (AMAP) within the Arctic Council. The workshop held in December 2012, aimed at identifying universal, accessible, and informative summary measures to demonstrate temporal changes in food and water security in the Arctic population [52]. The indicators of food and water security in an Arctic health context measured these temporal changes.…”
Section: Availability and Affordability Of Food In The Barents Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was a collaboration between the Arctic Human Health Expert Group, (AHHEG) and the Arctic Monitoring and Assessment Programme (AMAP) within the Arctic Council. The workshop held in December 2012, aimed at identifying universal, accessible, and informative summary measures to demonstrate temporal changes in food and water security in the Arctic population [52]. The indicators of food and water security in an Arctic health context measured these temporal changes.…”
Section: Availability and Affordability Of Food In The Barents Regionmentioning
confidence: 99%
“…These indicators can be measured for the countries of the Barents region; they promote the proportion of traditional foods in diet and the non-monetary accessibility to food when the indigenous population of this region are considered. The identified alternative measures of non-monetary food accessibility discussed were: the presence of hunter/fisher/collector/herder in families/households, accessibility of hunting/fishing/collecting/herding equipment, accessibility of sufficient hunting/fishing/collecting/herding land areas, environmental conditions suitable for hunting/fishing/collecting/herding, and the coping strategies to obtain traditional foods [52]. The other important indicators that promotes food security include healthy weight, monetary food costs, food-borne diseases, and food-related contaminants.…”
Section: Availability and Affordability Of Food In The Barents Regionmentioning
confidence: 99%
“…The emissions of air pollutants and wastewater discharge will increase and mostly be emitted around existing industrial sites and human settlements. Due to the environmental disruptions of traditional sources of food and water, circumpolar communities have become increasingly vulnerable to economic insecurity [47]. Morozova et al [48], Erokhin [49], and Liefert and Liefert [50] reported degrading purchasing power of population in Russia, which resulted in the redistribution of family means in favor of food, as well as a shift to less expensive food products and more affordable sources of proteins of lower quality and nutrition value [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroclimatic changes in the high‐latitude region, including both surface air temperature ( T ) and the water variables of precipitation ( P ), evapotranspiration ( ET ), and runoff ( R ), can lead to ecosystem regime shifts (Karlsson et al, ; Wrona et al, ); infrastructure damages (Instanes et al, ); and critical changes to water resources (Nilsson, Berner et al, ), water security (Bring, Jarsjö, & Destouni, ), and health (Daley et al, ; Evengard et al, ; Martin et al, ). Furthermore, local changes propagate with R and ET to affect the ocean (Carmack et al, ), atmosphere (Vihma et al, ), vegetation (Pearson et al, ), sedimentation rates and fish migration (Chalov et al, ), carbon releases from thawed permafrost (Schuur et al, ), and ocean‐biomass production by waterborne nutrient loading from land to sea (Prowse et al, ).…”
Section: Introductionmentioning
confidence: 99%